Рушійні сили навчального процесу в сучасній вищій школі - Власов, В. І. (ХНУРЕ, 2023)
This work examines the driving forces of the educational process in modern higher education, focusing on four main factors: technological advancements, global mindset, personalized learning, and soft skills. Technological innovations have revolutionized learning, making education more accessible and efficient. The interconnected nature of the global landscape necessitates a global mindset, while the shift towards personalized learning addresses diverse student needs. Additionally, the increasing emphasis on soft skills prepares students for success in the ever-evolving job market. These factors collectively shape the future of higher education, ensuring its continued relevance and efficacy.